Factsheet on capacities in agricultural higher education: Université du Burundi Faculté d’Agronomie et Bio-Ingenierie - Tailor, Anish; Magne Domgho, Léa Vicky; Beintema, Nienke M. (Regional Universities Forum for Capacity Building in Agriculture, 2018)
Credible quantitative and qualitative information on existing capacities in agricultural higher education agencies in Africa are crucial for strategic planning, policy formulation, setting priorities and benchmarks, measuring progress toward benchmarks, and identifying capacity gaps. Decisionmakers require a solid understanding of existing staffing and student capacities in the higher education sector, as well as in the wider agricultural innovation systems in Africa south of the Sahara. Access to such information supports effective policymaking to address capacity issues in higher education, agricultural research, extension, and other areas. Such information remains extremely limited, however. To fill this need, the International Food Policy Research Institute’s Agricultural Science and Technology Indicators (ASTI/IFPRI) and the Regional Universities Forum for Capacity Building in Agriculture (RUFORUM) initiated a partnership to pilot the collection of this type of data for RUFORUM’s member universities. This factsheet presents the available data results for Africa University, Faculty of Agriculture and Natural Resources. An online version of the data is available via the Portal on Agricultural Capacity in RUFORUM Universities: www.asti.cgiar.org/RUFORUM.